2022
DOI: 10.34067/kid.0002942022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Manifestations in Patients with Autosomal Dominant Polycystic Kidney Disease (ADPKD): A Single-Center Study

Abstract: Background: ADPKD is the most common monogenetic kidney disease and results in kidney failure in over 75% of affected individuals. As a systemic disorder, ADPKD is associated with a variety of extrarenal manifestations affecting the majority of patients including cardiac manifestations. We characterized the cardiac involvement in ADPKD patients from the German AD(H)PKD registry and compared them to kidney donor candidates as controls. Methods: In this single-center cohort study, we evaluated 141 ADPKD (44.17 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Chapman and colleagues reported in 1997 that 41% of patients with ADPKD with a similar eGFR profile and mean age of 41 years had cardiac hypertrophy as measured by left ventricular mass index by echocardiography. 4 In contrast to Arjune and colleagues, 3 baseline analysis of the HALT-polycystic kidney disease (PKD) study of 543 patients with ADPKD reported a much lower prevalence of LVH of 4%. 5 , 6 Where does this jarring discrepancy in reported incidences come from?…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Chapman and colleagues reported in 1997 that 41% of patients with ADPKD with a similar eGFR profile and mean age of 41 years had cardiac hypertrophy as measured by left ventricular mass index by echocardiography. 4 In contrast to Arjune and colleagues, 3 baseline analysis of the HALT-polycystic kidney disease (PKD) study of 543 patients with ADPKD reported a much lower prevalence of LVH of 4%. 5 , 6 Where does this jarring discrepancy in reported incidences come from?…”
mentioning
confidence: 93%
“… 2 A nuanced understanding of the cardiac phenotype within ADPKD population is required to inform clinical practice. The recent study by Arjune and colleagues 3 of 141 patients with ADPKD from the German AD(H)PKD registry provides a comprehensive echocardiographic examination of cardiovascular function in the tolvaptan era of ADPKD treatment.…”
mentioning
confidence: 99%
See 3 more Smart Citations